Hydrogen-containing glass-based articles having high-indentation cracking thresholds
By forming a hydrogen-containing layer in the glass substrate, the problem of high-destructive material required for portable electronic devices is solved, and the high Vickers crack initiation threshold of glass products is achieved, which significantly improves the material's anti-indentation performance.
Patent Information
- Application Number
- CN202211037030.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-05-08
- Filing Date
- 2018-11-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2038-11-16
AI Technical Summary
The prior art is difficult to provide materials for portable electronic devices, with higher resistance to destruction and complexity to accommodate the continuous shrinkage and thinning of these devices.
By forming a hydrogen-containing layer in the glass substrate, the indentation resistance of the glass is enhanced by utilizing the characteristic of gradually decreasing hydrogen concentration from the surface. The method includes exposing the glass substrate to a high humidity environment, permeating hydrogen substances and forming a hydrogen-containing layer, thereby increasing the Vickers crack-initiating threshold of the glass.
The high indentation resistance of glass products is achieved, and the Vickers crack initiation threshold reaches 1kgf or higher, which significantly improves the resistance of the material.
Smart Images

Figure CN115231822B_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with application date 201880074555.7, application date November 16, 2018, and name “Products based on hydrogen-containing glass with high pressure mark cracking threshold”. Background Art
[0002] Related Applications
[0003] This application claims priority to U.S. Provisional Application Serial No. 62 / 587,872 filed on November 17, 2017 (which is hereby based on and incorporated herein by reference in its entirety) and Netherlands Application No. 2020896 filed on May 8, 2018 (which is hereby based on and incorporated herein by reference in its entirety). Technical Field
[0004] The present disclosure relates to glass-based articles containing hydrogen, glass compositions for forming glass-based articles, and methods of forming glass-based articles. Background Art
[0006] Portable electronic devices, such as smartphones, tablets, and wearable devices such as watches and fitness trackers, continue to become smaller and more complex. As a result, the materials conventionally used on at least one exterior surface of such portable electronic devices continue to become more complex. For example, as portable electronic devices become smaller and thinner to meet consumer demands, display covers and housings for these portable electronic devices also become smaller and thinner, resulting in higher performance requirements for the materials used to form these components.
[0007] Therefore, there is a need for materials that exhibit higher performance (eg, damage resistance) for use in portable electronic devices. Summary of the invention
[0008] In aspect (1), a glass-based article is provided. The glass-based article comprises: SiO2, Al2O3, and P2O5; and a hydrogen-containing layer extending from a surface of the glass-based article to a layer depth. The hydrogen concentration of the hydrogen-containing layer decreases from a maximum hydrogen concentration to the layer depth, and the layer depth is greater than 5 μm.
[0009] In aspect (2), there is provided the glass-based article of aspect (1), wherein the glass-based article has a Vickers crack initiation threshold greater than or equal to 1 kgf.
[0010] In aspect (3), there is provided a glass-based article of aspect (1) or (2), wherein the depth of layer is greater than or equal to 10 μm.
[0011] In aspect (4), there is provided the glass-based article of any one of aspects (1) to (3), wherein the maximum hydrogen concentration is located at a surface of the glass-based article.
[0012] In aspect (5), there is provided a glass-based article of any one of aspects (1) to (4), further comprising at least one of the following: Li2O, Na2O, K2O, Cs2O, and Rb2O.
[0013] In aspect (6), there is provided the glass-based article of any one of aspects (1) to (5), further comprising K2O.
[0014] In aspect (7), a glass-based article of any one of aspects (1) to (6) is provided, wherein the center of the glass-based article contains: greater than or equal to 45 mol% to less than or equal to 75 mol% SiO2, greater than or equal to 3 mol% to less than or equal to 20 mol% Al2O3, greater than or equal to 6 mol% to less than or equal to 15 mol% P2O5, and greater than or equal to 6 mol% to less than or equal to 25 mol% K2O.
[0015] In aspect (8), a glass-based article of any one of aspects (1) to (6) is provided, wherein the center of the glass-based article comprises: greater than or equal to 45 mol% to less than or equal to 75 mol% SiO2, greater than or equal to 3 mol% to less than or equal to 20 mol% Al2O3, greater than or equal to 4 mol% to less than or equal to 15 mol% P2O5, and greater than or equal to 11 mol% to less than or equal to 25 mol% K2O.
[0016] In aspect (9), a glass-based article of any one of aspects (1) to (6) is provided, wherein the center of the glass-based article comprises: greater than or equal to 55 mol% to less than or equal to 69 mol% SiO2, greater than or equal to 5 mol% to less than or equal to 15 mol% Al2O3, greater than or equal to 6 mol% to less than or equal to 10 mol% P2O5, and greater than or equal to 10 mol% to less than or equal to 20 mol% K2O.
[0017] In aspect (10), a glass-based article of any one of aspects (7) to (9) is provided, wherein the center of the glass-based article comprises: greater than or equal to 0 mol % to less than or equal to 10 mol % Cs2O, and greater than or equal to 0 mol % to less than or equal to 10 mol % Rb2O.
[0018] In aspect (11), there is provided the glass-based article of any one of aspects (1) to (10), wherein the glass-based article is substantially free of at least one of lithium and sodium.
[0019] In aspect (12), the glass-based article of any of aspects (1) to (11) is provided, further comprising a compressive stress layer extending from a surface of the glass-based article into the glass-based article to a compressive depth.
[0020] In aspect (13), the glass-based article of aspect (12) is provided, wherein the compressive stress layer comprises a compressive stress of at least about 100 MPa, and the compression depth is at least about 75 μm.
[0021] In aspect (14), a consumer electronic product is provided. The consumer electronic product comprises: a housing comprising a front surface, a back surface, and a side surface; an electronic component at least partially located within the housing, the electronic component comprising at least a controller, a memory, and a display, the display being located on or adjacent to the front surface of the housing; and a cover substrate disposed above the display. At least a portion of at least one of the housing or the cover substrate comprises the glass-based article of any one of aspects (1) to (13).
[0022] In aspect (15), a glass is provided, comprising: greater than or equal to 45 mol% and less than or equal to 75 mol% SiO2, greater than or equal to 3 mol% and less than or equal to 20 mol% Al2O3, greater than or equal to 6 mol% and less than or equal to 15 mol% P2O5, and greater than or equal to 6 mol% and less than or equal to 25 mol% K2O.
[0023] In aspect (16), a glass according to aspect (15) is provided, comprising: greater than or equal to 55 mol % to less than or equal to 69 mol % SiO2, greater than or equal to 5 mol % to less than or equal to 15 mol % Al2O3, greater than or equal to 6 mol % to less than or equal to 10 mol % P2O5, and greater than or equal to 10 mol % to less than or equal to 20 mol % K2O.
[0024] In aspect (17), the glass of aspect (15) or (16) is provided, which further comprises: greater than or equal to 0 mol % to less than or equal to 10 mol % Cs2O, and greater than or equal to 0 mol % to less than or equal to 10 mol % Rb2O.
[0025] In aspect (18), the glass of any one of aspects (15) to (17) is provided, wherein the glass is substantially free of lithium.
[0026] In aspect (19), there is provided the glass of any one of aspects (15) to (18), wherein the glass is substantially free of sodium.
[0027] In aspect (20), a glass of any one of aspects (15) to (19) is provided, comprising: greater than or equal to 58 mol % to less than or equal to 63 mol % SiO2, greater than or equal to 7 mol % to less than or equal to 14 mol % Al2O3, greater than or equal to 7 mol % to less than or equal to 10 mol % P2O5, and greater than or equal to 15 mol % to less than or equal to 20 mol % K2O.
[0028] In aspect (21), there is provided the glass of any one of aspects (15) to (20), wherein the glass has a Vickers crack initiation threshold of greater than or equal to 5 kgf.
[0029] In aspect (22), there is provided the glass of any one of aspects (15) to (21), further comprising at least one of the following: Li2O, Na2O, Cs2O, and Rb2O.
[0030] In aspect (23), a glass is provided, comprising: greater than or equal to 45 mol% and less than or equal to 75 mol% SiO2, greater than or equal to 3 mol% and less than or equal to 20 mol% Al2O3, greater than or equal to 4 mol% and less than or equal to 15 mol% P2O5, and greater than or equal to 11 mol% and less than or equal to 25 mol% K2O.
[0031] In aspect (24), a glass of aspect (23) is provided, comprising: greater than or equal to 55 mol % to less than or equal to 69 mol % SiO2, greater than or equal to 5 mol % to less than or equal to 15 mol % Al2O3, greater than or equal to 5 mol % to less than or equal to 10 mol % P2O5, and greater than or equal to 11 mol % to less than or equal to 20 mol % K2O.
[0032] In aspect (25), the glass of aspect (23) or (24) is provided, which further comprises: greater than or equal to 0 mol % to less than or equal to 10 mol % Cs2O, and greater than or equal to 0 mol % to less than or equal to 10 mol % Rb2O.
[0033] In aspect (26), the glass of any one of aspects (23) to (25) is provided, wherein the glass is substantially free of lithium.
[0034] In aspect (27), the glass of any one of aspects (23) to (26) is provided, wherein the glass is substantially free of sodium.
[0035] In aspect (28), a glass of any one of aspects (23) to (27) is provided, comprising: greater than or equal to 58 mol % to less than or equal to 63 mol % SiO2, greater than or equal to 7 mol % to less than or equal to 14 mol % Al2O3, greater than or equal to 7 mol % to less than or equal to 10 mol % P2O5, and greater than or equal to 15 mol % to less than or equal to 20 mol % K2O.
[0036] In aspect (29), there is provided the glass of any one of aspects (23) to (28), wherein the glass has a Vickers crack initiation threshold greater than or equal to 5 kgf.
[0037] In aspect (30), the glass of any one of aspects (23) to (29) is provided, further comprising at least one of the following: Li2O, Na2O, Cs2O, and Rb2O.
[0038] In aspect (31), a method is provided. The method includes: exposing a glass-based substrate to an environment with a relative humidity greater than or equal to 75% to form a glass-based article, the glass-based article having a hydrogen-containing layer extending from a surface of the glass-based article to a layer depth. The glass-based substrate comprises SiO2, Al2O3, and P2O5. The hydrogen concentration of the hydrogen-containing layer decreases from a maximum hydrogen concentration to the layer depth, and the layer depth is greater than 5 μm.
[0039] In aspect (32), a method of aspect (31) is provided, wherein the composition of the glass-based substrate comprises: greater than or equal to 55 mol% to less than or equal to 69 mol% SiO2, greater than or equal to 5 mol% to less than or equal to 15 mol% Al2O3, greater than or equal to 6 mol% to less than or equal to 10 mol% P2O5, and greater than or equal to 10 mol% to less than or equal to 20 mol% K2O.
[0040] In aspect (33), a method of aspect (31) is provided, wherein the composition of the glass-based substrate comprises: greater than or equal to 45 mol% to less than or equal to 75 mol% SiO2, greater than or equal to 3 mol% to less than or equal to 20 mol% Al2O3, greater than or equal to 4 mol% to less than or equal to 15 mol% P2O5, and greater than or equal to 11 mol% to less than or equal to 25 mol% K2O.
[0041] In aspect (34), a method of aspect (31) is provided, wherein the composition of the glass-based substrate comprises: greater than or equal to 45 mol% to less than or equal to 75 mol% SiO2, greater than or equal to 3 mol% to less than or equal to 20 mol% Al2O3, greater than or equal to 6 mol% to less than or equal to 15 mol% P2O5, and greater than or equal to 6 mol% to less than or equal to 25 mol% K2O.
[0042] In aspect (35), a method according to any one of aspects (31) to (34) is provided, wherein the glass-based substrate further comprises: greater than or equal to 0 mol % to less than or equal to 10 mol % Cs2O, and greater than or equal to 0 mol % to less than or equal to 10 mol % Rb2O.
[0043] In aspect (36), the method of any one of aspects (31) to (35) is provided, further comprising at least one of the following: Li2O, Na2O, Cs2O, and Rb2O.
[0044] In aspect (37), the method of any one of aspects (31) to (36) is provided, wherein the glass-based substrate is substantially free of at least one of lithium and sodium.
[0045] In aspect (38), the method of any one of aspects (31) to (37) is provided, wherein the temperature at which the exposing occurs is greater than or equal to 70°C.
[0046] In aspect (39), the method of any one of aspects (31) to (38) is provided, wherein the glass-based article has a Vickers crack initiation threshold greater than or equal to 1 kgf.
[0047] These and other aspects, advantages and salient features will be apparent from the following detailed description, the accompanying drawings and the appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 is a cross-sectional representation of a glass-based article according to an embodiment.
[0049] Figure 2A is a plan view of an exemplary electronic device incorporating any of the glass-based articles disclosed herein.
[0050] Figure 2B yes Figure 2A A perspective view of an exemplary electronic device.
[0051] Figure 3 is the hydrogen concentration measurements made by SIMS for a glass-based article formed from a glass-based substrate having the composition of Example 1 as a function of depth below the surface.
[0052] Figure 4 is a photograph of a 5 kgf Vickers indentation in a glass-based substrate having the composition of Example 1 before exposure to an aqueous environment.
[0053] Figure 5 is a photograph of a 10 kgf Vickers indentation of a glass-based substrate having the composition of Example 1 before exposure to an aqueous environment.
[0054] Figure 6 is a photograph of a 5 kgf Vickers indentation in a glass-based article formed by exposing a glass-based substrate having the composition of Example 1 to an aqueous environment.
[0055] Figure 7 is a photograph of a 10 kgf Vickers indentation in a glass-based article formed by exposing a glass-based substrate having the composition of Example 1 to an aqueous environment.
[0056] Figure 8 is a photograph of a 20 kgf Vickers indentation in a glass-based article formed by exposing a glass-based substrate having the composition of Example 1 to an aqueous environment.
[0057] Fig. 9 is a graph of hydroxyl (BOH) concentration as a function of depth from the surface of a 0.5 mm thick glass article after exposure to an aqueous environment according to an embodiment.
[0058] Fig.10 is a graph of hydroxyl (BOH) concentration as a function of depth from the surface for a 1.0 mm thick glass article after exposure to an aqueous environment according to an embodiment.
[0059] Fig.11 is a side view of the ring-on-ring test equipment. DETAILED DESCRIPTION
[0060] In the following description, the same reference numerals denote similar or corresponding parts in the several views shown in the accompanying drawings. It is also understood that, unless otherwise indicated, terms such as "top", "bottom", "outward", "inward", etc. are convenient words and do not constitute limitations on the terms. Unless otherwise specified, the listed numerical ranges include both the upper and lower limits of the ranges, as well as any sub-ranges between the ranges. Unless otherwise specified, the indefinite articles "one" or "a kind" and their corresponding definite articles "the" used herein mean "at least one" or "one or more". It is also understood that the various features disclosed in the specification and the drawings can be used in any and all combinations.
[0061] As used herein, the term "glass-based" is used in its broadest sense to include any object made in whole or in part of glass (including glass-ceramics, which contain a crystalline phase and a residual amorphous glass phase). Unless otherwise stated, all components of the glasses described herein are expressed in mole percent (mol%), and the composition is calculated as oxides. Unless otherwise stated, all temperatures are expressed in degrees Celsius (° C.).
[0062] It is noted that the terms "substantially" and "about" may be used herein to represent the degree of inherent uncertainty that may result from any quantitative comparison, value, measurement, or other representation. These terms are also used herein to represent that a value expressed in a quantity may deviate from a stated reference value to a certain extent without resulting in a change in the basic function of the subject matter under consideration. For example, a glass that is "substantially free of K2O" is a glass in which K2O is not actively added or dosed into the glass, but may be present as a contaminant in very small amounts, for example, less than about 0.01 mol%. As used herein, when the term "about" is used to modify a value, the specific value is also disclosed. For example, the term "greater than about 10 mol%" also discloses "greater than or equal to 10 mol%".
[0063] Reference will now be made in detail to various embodiments, examples of which are illustrated in the accompanying examples and drawings.
[0064] The glass-based articles disclosed herein include a hydrogen-containing layer extending from the surface of the article to a layer depth. The hydrogen-containing layer includes a hydrogen concentration that decreases from a maximum hydrogen concentration of the glass-based article to the layer depth. In some embodiments, the maximum hydrogen concentration may be located at the surface of the glass-based article. The glass-based article exhibits a high Vickers indentation cracking threshold (e.g., greater than or equal to 1 kgf) without using conventional strengthening methods (e.g., ion exchange of a pair of alkaline ions or thermal tempering). The high Vickers indentation cracking threshold exhibited by the glass-based article means high damage resistance.
[0065] A glass-based article may be formed by exposing a glass-based substrate to a water vapor-containing environment, thereby allowing hydrogen species to penetrate the glass-based substrate and form a glass-based article having a hydrogen-containing layer. As used herein, hydrogen species include molecular water, hydroxyl groups, hydrogen ions, and hydronium ions. The composition of the glass-based substrate may be selected to promote interdiffusion of hydrogen species into the glass. As used herein, the term "glass-based substrate" refers to a precursor prior to exposure to a water vapor environment for forming a glass-based article including a hydrogen-containing layer. Similarly, the term "glass-based article" refers to an article including a hydrogen-containing layer after exposure occurs.
[0066] like Figure 1A representative cross-section of a glass-based article 100 according to some embodiments is shown. The glass-based article 100 has a thickness t extending between a first surface 110 and a second surface 112. A first hydrogen-containing layer 120 extends from the first surface 110 to a first layer depth, wherein the first layer depth has a depth d1 measured from the first surface 110 into the glass-based article 100. A second hydrogen-containing layer 122 extends from the second surface 112 to a second layer depth, wherein the second layer depth has a depth d2 measured from the second surface 112 into the glass-based article 100. Between the first layer depth and the second layer depth there is a region 130 that is free of added hydrogen species.
[0067] The depth of layer (DOL) of the hydrogen-containing layer of the glass-based article may be greater than 5 μm. In some embodiments, the depth of layer may be greater than or equal to 10 μm, for example, greater than or equal to 15 μm, greater than or equal to 20 μm, greater than or equal to 25 μm, greater than or equal to 30 μm, greater than or equal to 35 μm, greater than or equal to 40 μm, greater than or equal to 45 μm, greater than or equal to 50 μm, greater than or equal to 55 μm, greater than or equal to 60 μm, greater than or equal to 65 μm, greater than or equal to 70 μm, greater than or equal to 75 μm, greater than or equal to 80 μm, greater than or equal to 85 μm, greater than or equal to 90 μm, greater than or equal to 95 μm, greater than or equal to 100 μm, greater than or equal to 105 μm, or greater than or equal to 100 μm. μm, greater than or equal to 110μm, greater than or equal to 115μm, greater than or equal to 120μm, greater than or equal to 125μm, greater than or equal to 130μm, greater than or equal to 135μm, greater than or equal to 140μm, greater than or equal to 145μm, greater than or equal to 150μm, greater than or equal to 155μm, greater than or equal to 160μm, greater than or equal to 165μm, greater than or equal to 170μm, greater than or equal to 175μm, greater than or equal to 180μm, greater than or equal to 185μm, greater than or equal to 190μm, greater than or equal to 195μm, greater than or equal to 200μm or greater. In some embodiments, the layer depth can be greater than 5 μm to less than or equal to 205 μm, for example: greater than or equal to 10 μm to less than or equal to 200 μm, greater than or equal to 15 μm to less than or equal to 200 μm, greater than or equal to 20 μm to less than or equal to 195 μm, greater than or equal to 25 μm to less than or equal to 190 μm, greater than or equal to 30 μm to less than or equal to 185 μm, greater than or equal to 35 μm to less than or equal to 180 μm, greater than or equal to 40 μm to less than or equal to 175 μm, greater than or equal to 45 μm to less than or equal to 170 μm, greater than or equal to 50 μm to less than or equal to 165 μm, greater than or equal to 55 μm to less than or equal to 165 μm, 160 μm, 60 μm or more to 155 μm or less, 65 μm or more to 150 μm or less, 70 μm or more to 145 μm or less, 75 μm or more to 140 μm or less, 80 μm or more to 135 μm or less, 85 μm or more to 130 μm or less, 90 μm or more to 125 μm or less, 95 μm or more to 120 μm or less, 100 μm or more to 115 μm or less, 105 μm or more to 110 μm or less, or any subrange formed by any of these endpoints. Generally, the glass-based article exhibits a depth of layer greater than or equal to the depth of layer that can be produced by exposure to an ambient environment.
[0068] The depth of layer (DOL) of the hydrogen-containing layer of the glass-based article may be greater than 0.005t, where t is the thickness of the glass-based article. In some embodiments, the layer depth can be greater than or equal to 0.010t, for example: greater than or equal to 0.015t, greater than or equal to 0.020t, greater than or equal to 0.025t, greater than or equal to 0.030t, greater than or equal to 0.035t, greater than or equal to 0.040t, greater than or equal to 0.045t, greater than or equal to 0.050t, greater than or equal to 0.055t, greater than or equal to 0.060t, greater than or equal to 0.065t, greater than or equal to 0.070t, greater than or equal to 0.075t, greater than or equal to 0.080t, greater than or equal to 0.085t, greater than or equal to 0.090t, greater than or equal to 0.095t, greater than or equal to 0.10t, greater than or equal to 0.15t, greater than or equal to 0.20t, or greater. In some embodiments, the DOL may be greater than 0.005t to less than or equal to 0.205t, for example: greater than or equal to 0.010t to less than or equal to 0.200t, greater than or equal to 0.015t to less than or equal to 0.195t, greater than or equal to 0.020t to less than or equal to 0.190t, greater than or equal to 0.025t to less than or equal to 0.185t, greater than or equal to 0.030t to less than or equal to 0.180t, greater than or equal to 0.035t to less than or equal to 0.175t, greater than or equal to 0.040t to less than or equal to 0.170t, greater than or equal to 0.045t to less than or equal to 0.165t, greater than or equal to 0.050t to less than or equal to 0.160t, greater than or equal to 0.050t to less than or equal to 0.160t, greater than or equal to 0.060t, greater than or equal to 0.070t, greater than or equal to 0.080t, greater than or equal to 0.085t, greater than or equal to 0.090t, greater than or equal to 0.1 ... The invention relates to a range of t to t, wherein the present invention is preferably t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t, wherein the present invention is a range of t to t,
[0069] The depth of layer and hydrogen concentration are measured by secondary ion mass spectrometry (SIMS) techniques known in the art. The SIMS technique is capable of measuring the hydrogen concentration at a given depth, but is unable to distinguish between hydrogen species present in a glass-based article. For this reason, all hydrogen species contribute to the hydrogen concentration measured by SIMS. As used herein, the depth of layer (DOL) refers to the first depth below the surface of a glass-based article where the hydrogen concentration is equal to the hydrogen concentration at the center of the glass-based article. This definition takes into account the hydrogen concentration of the glass-based substrate before treatment, so that the depth of layer refers to the depth of hydrogen added by the treatment process. In practice, the hydrogen concentration at the center of a glass-based article can be approximated as the hydrogen concentration at a depth at which the hydrogen concentration from the surface of the glass-based article becomes substantially constant, because the hydrogen concentration is not expected to change between this depth and the center of the glass-based article. This approximation enables the determination of the DOL without measuring the hydrogen concentration over the entire depth of the glass-based article.
[0070] In some embodiments, the entire thickness of the glass-based article may be part of the hydrogen-containing layer. Such glass-based articles may be produced when the glass-based substrate treatment continues for a sufficient time and the conditions are sufficient to allow the hydrogen species to diffuse from each exposed surface to the center of the glass-based article. In some embodiments, when the surface of the glass-based article is exposed to the same treatment conditions, the minimum hydrogen concentration may be located at half the thickness of the glass-based article, so that the hydrogen-containing layer meets at the center of the glass-based article. In such embodiments, the DOL may be located at half the thickness of the glass-based article. In some embodiments, the glass-based article may not include an area that does not contain added hydrogen species. In some embodiments, the glass-based article may be treated in a humid environment so that the concentration of the added hydrogen species is balanced throughout the glass-based article, and the hydrogen concentration does not change with the depth below the surface of the glass-based article. Glass-based articles according to such embodiments will not exhibit a DOL as defined herein because the hydrogen concentration at the center of the glass-based article will be equal to the hydrogen concentration at all other depths.
[0071] Glass-based articles are highly resistant to Vickers indentation cracking. High Vickers indentation cracking resistance gives glass-based articles high resistance to damage. Without wishing to be bound by any particular theory, the water content of glass-based articles can reduce the local viscosity of the hydrogen-containing layer, so that local flow occurs instead of cracking. The Vickers indentation cracking threshold of glass-based articles is achieved without the use of conventional strengthening techniques (e.g., exchanging smaller alkali ions in the glass with larger alkali ions, thermal tempering, or lamination of glass layers with mismatched thermal expansion coefficients). Glass-based articles exhibit the following Vickers indentation cracking thresholds: greater than or equal to 1 kgf, for example, greater than or equal to 2 kgf, greater than or equal to 3 kgf, greater than or equal to 4 kgf, greater than or equal to 5 kgf, greater than or equal to 6 kgf, greater than or equal to 7 kgf, greater than or equal to 8 kgf, greater than or equal to 9 kgf, greater than or equal to 10 kgf, greater than or equal to 11 kgf, greater than or equal to 12 kgf, greater than or equal to 13 kgf, greater than or equal to 14 kgf, greater than or equal to 1 5kgf, 16kgf or more, 17kgf or more, 18kgf or more, 19kgf or more, 20kgf or more, 21kgf or more, 22kgf or more, 23kgf or more, 24kgf or more, 25kgf or more, 26kgf or more, 27kgf or more, 28kgf or more, 29kgf or more, 30kgf or more, or more. In some embodiments, the glass-based article exhibits a Vickers indentation cracking threshold of greater than or equal to 1 kgf to less than or equal to 30 kgf, for example: greater than or equal to 2 kgf to less than or equal to 29 kgf, greater than or equal to 3 kgf to less than or equal to 28 kgf, greater than or equal to 4 kgf to less than or equal to 27 kgf, greater than or equal to 5 kgf to less than or equal to 26 kgf, greater than or equal to 6 kgf to less than or equal to 25 kgf, greater than or equal to 7 kgf to less than or equal to 24 kgf, greater than or equal to 8 kgf. gf to less than or equal to 23kgf, greater than or equal to 9kgf to less than or equal to 22kgf, greater than or equal to 10kgf to less than or equal to 21kgf, greater than or equal to 11kgf to less than or equal to 20kgf, greater than or equal to 12kgf to less than or equal to 19kgf, greater than or equal to 13kgf to less than or equal to 18kgf, greater than or equal to 14kgf to less than or equal to 17kgf, greater than or equal to 15kgf to less than or equal to 16kgf, or any sub-range formed by any of these endpoints.
[0072] The Vickers crack initiation threshold (or indentation crushing threshold) is measured by a Vickers indenter. The Vickers crack initiation threshold is a measure of the resistance of glass to indentation damage. The test involves the use of a square pyramid-shaped diamond indenter with an angle of 136° between faces, called a Vickers indenter. The Vickers indenter is the same as that used for standard microhardness testing (as described in ASTM-E384-11). A minimum of 5 specimens are selected to represent the glass type and / or sample of interest. For each specimen, multiple groups of 5 indentations are introduced on the specimen surface. Each group of 5 indentations is introduced with a given load, and each single indentation is spaced at least 5mm apart and not less than 5mm near the edge of the specimen. For the case where the test load is ≥2kg, an indenter load / unload rate of 50kg / minute is used. For the case where the test load is <2kg, a rate of 5kg / minute is used. A 10-second dwell time (i.e., holding time) is used at the target load. During the dwell time, the machine maintains load control. After a period of at least 12 hours, a compound microscope is used to examine the indentation with reflected light at a magnification of 500X. Then, for each indentation, record the presence or absence of median / radial cracks (cracks extending from the indentation along a plane perpendicular to the major surface of the article), or specimen crushing. Note that since this test is interested in the formation of median / radial cracks or specimen crushing, the formation of transverse cracks (cracks extending along a plane parallel to the major surface of the article) is not considered an indication of exhibiting threshold behavior. The specimen threshold is defined as the midpoint of the lowest continuous indentation load, where more than 50% of the individual indentations that meet the threshold are grouped together. For example, if the indentation caused by a 5kg load for 2 individual specimens (40%) out of 5 specimens exceeds the threshold, and the indentation caused by a 6kg load for 3 individual specimens (60%) out of 5 specimens exceeds the threshold, the specimen threshold will be defined as greater than 5kg. For each sample, the range of all specimen midpoints (lowest value to highest value) can also be recorded. The pre-test environment, test environment, and post-test environment are controlled at 23±2℃ and 50±5%RH to minimize changes in the fatigue (stress corrosion) behavior of the specimens.
[0073] Without wishing to be bound by any particular theory, the hydrogen-containing layer of the glass-based article may be the result of interdiffusion of hydrogen species with ions contained in the composition of the glass-based substrate. + and / or H + ) can replace alkaline ions contained in the glass-based substrate composition to form a glass-based article. The size of the alkaline ion replaced by the hydrogen-containing species contributes to the diffusivity of the hydrogen-containing species in the glass-based substrate, and larger alkaline ions create larger interstitial spaces that facilitate interdiffusion mechanisms. For example, hydronium ions (H3O +) has an ionic radius close to that of potassium and much larger than that of lithium. It was observed that the diffusivity of hydrogen-containing species in the glass-based substrate was significantly higher by 2 orders of magnitude when the glass-based substrate contained potassium compared to the glass-based substrate containing lithium. This observed behavior may also indicate that hydronium ions are the primary monovalent hydrogen-containing species diffusing into the glass-based substrate. Table 1 below records the ionic radii of alkaline ions and hydronium ions. As shown in Table 1, the ionic radii of rubidium and cesium are significantly larger than that of hydronium ions, which may result in a higher hydrogen diffusivity than that observed for potassium.
[0074] Table I
[0075]
[0076] In some embodiments, replacing alkaline ions in a glass-based substrate with hydrogen-containing ions can generate a compressive stress layer that extends from the surface of the glass-based article into the glass-based article to a depth of compression. As used herein, depth of compression (DOC) refers to the depth at which stress within the glass-based article changes from compression to tension. Therefore, the glass-based article also contains a tensile stress region with a maximum central tension (CT), thereby balancing the forces in the glass-based article. Without wishing to be bound by any theory, the compressive stress region may be the result of the exchange of hydrogen-containing ions that have a larger ionic radius than the ions they replace.
[0077] In some embodiments, the compressive stress layer may include a compressive stress greater than or equal to 100 MPa, for example, greater than or equal to 105 MPa, greater than or equal to 110 MPa, greater than or equal to 115 MPa, greater than or equal to 120 MPa, greater than or equal to 125 MPa, greater than or equal to 130 MPa, greater than or equal to 135 MPa, or greater. In some embodiments, the compressive stress layer may include a compressive stress greater than or equal to 100 MPa to less than or equal to 150 MPa, for example, greater than or equal to 105 MPa to less than or equal to 145 MPa, greater than or equal to 110 MPa to less than or equal to 140 MPa, greater than or equal to 115 MPa to less than or equal to 135 MPa, greater than or equal to 120 MPa to less than or equal to 130 MPa, 125 MPa, or any sub-range formed by any of these endpoint values.
[0078] In some embodiments, the DOC of the compressive stress layer may be greater than or equal to 75 μm, for example, greater than or equal to 80 μm, greater than or equal to 85 μm, greater than or equal to 90 μm, greater than or equal to 95 μm, greater than or equal to 100 μm, or greater. In some embodiments, the DOC of the compressive stress layer may be greater than or equal to 75 μm to less than or equal to 115 μm, for example, greater than or equal to 80 μm to less than or equal to 110 μm, greater than or equal to 85 μm to less than or equal to 105 μm, greater than or equal to 90 μm to less than or equal to 100 μm, 95 μm, or any sub-range formed by any of these endpoint values.
[0079] In some embodiments, the DOC of the glass-based article can be greater than or equal to 0.05t, where t is the thickness of the glass-based article, for example: greater than or equal to 0.06t, greater than or equal to 0.07t, greater than or equal to 0.08t, greater than or equal to 0.09t, greater than or equal to 0.10t, greater than or equal to 0.11t, greater than or equal to 0.12t, or greater. In some embodiments, the glass-based article may have a DOC of greater than or equal to 0.05t to less than or equal to 0.20t, for example, greater than or equal to 0.06t to less than or equal to 0.19t, greater than or equal to 0.07t to less than or equal to 0.18t, greater than or equal to 0.08t to less than or equal to 0.17t, greater than or equal to 0.09t to less than or equal to 0.16t, greater than or equal to 0.10t to less than or equal to 0.15t, greater than or equal to 0.11t to less than or equal to 0.14t, greater than or equal to 0.12t to less than or equal to 0.13t, or any sub-range formed by any of these endpoint values.
[0080] In some embodiments, the glass-based article may have a CT greater than or equal to 10 MPa, for example, greater than or equal to 11 MPa, greater than or equal to 12 MPa, greater than or equal to 13 MPa, greater than or equal to 14 MPa, greater than or equal to 15 MPa, greater than or equal to 16 MPa, greater than or equal to 17 MPa, greater than or equal to 18 MPa, greater than or equal to 19 MPa, greater than or equal to 20 MPa, greater than or equal to 22 MPa, greater than or equal to 24 MPa, greater than or equal to 26 MPa, greater than or equal to 28 MPa, greater than or equal to 30 MPa, greater than or equal to 32 MPa, or greater. In some embodiments, the glass-based article can have a CT of greater than or equal to 10 MPa to less than or equal to 35 MPa, for example, greater than or equal to 11 MPa to less than or equal to 34 MPa, greater than or equal to 12 MPa to less than or equal to 33 MPa, greater than or equal to 13 MPa to less than or equal to 32 MPa, greater than or equal to 14 MPa to less than or equal to 32 MPa, greater than or equal to 15 MPa to less than or equal to 31 MPa, greater than or equal to 16 MPa to less than or equal to 30 MPa, greater than or equal to 17 MPa to less than or equal to 28 MPa, greater than or equal to 18 MPa to less than or equal to 26 MPa, greater than or equal to 19 MPa to less than or equal to 24 MPa, greater than or equal to 20 MPa to less than or equal to 22 MPa, or any sub-range formed by any of these endpoint values.
[0081] Compressive stress (including surface CS) is measured by a surface stress meter, using a commercial instrument such as the FSM-6000 (FSM) manufactured by Orihara Industrial Co., Ltd. (Japan). Surface stress measurements rely on accurate measurements of the stress-optical coefficient (SOC), which is related to the birefringence of the glass. SOC is then measured according to Scheme C (Glass Disc Method) described in ASTM Standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient", the entire text of which is incorporated herein by reference. DOC is measured by FSM. Maximum central tension (CT) values are measured using a scattered light polarizer (SCALP) technique known in the art.
[0082] A glass-based article may be formed from a glass-based substrate having any suitable composition. The composition of the glass-based substrate may be specifically selected to promote the diffusion of hydrogen-containing species, so that a glass-based article comprising a hydrogen-containing layer may be efficiently formed. In some embodiments, the glass-based substrate may have a composition comprising SiO2, Al2O3, and P2O5. In some embodiments, the glass-based substrate may additionally comprise an alkali metal oxide, such as at least one of Li2O, Na2O, K2O, Rb2O, and Cs2O. In some embodiments, the glass-based substrate may be substantially free of or free of at least one of lithium and sodium. In some embodiments, after the hydrogen-containing species diffuse into the glass-based substrate, the glass-based article may have a bulk composition that is approximately the same as the composition of the glass-based substrate. In some embodiments, the hydrogen species may not diffuse into the center of the glass-based article. In other words, the center of the glass-based article is the area least affected by the water vapor treatment. For this reason, the composition of the center of the glass-based article may be substantially the same or the same as the composition of the glass-based substrate before treatment in an aqueous environment.
[0083] The glass-based substrate may include any suitable amount of SiO2. SiO2 is the most predominant component, and thus, SiO2 is the predominant component of the glass network formed by the glass composition. If the concentration of SiO2 in the glass composition is too high, the formability of the glass composition may decrease because the higher SiO2 concentration increases the difficulty of melting the glass, which in turn has a negative impact on the formability of the glass. In some embodiments, the amount of SiO2 included in the glass-based substrate may be greater than or equal to 45 mol% to less than or equal to 75 mol%, for example: greater than or equal to 46 mol% to less than or equal to 74 mol%, greater than or equal to 47 mol% to less than or equal to 73 mol%, greater than or equal to 48 mol% to less than or equal to 72 mol%, greater than or equal to 49 mol% to less than or equal to 71 mol%, greater than or equal to 50 mol% to less than or equal to 70 mol%, greater than or equal to 51 mol% to less than or equal to 69 mol%, greater than or equal to 52 % to less than or equal to 68 mol%, 53 mol% to less than or equal to 67 mol%, 54 mol% to less than or equal to 66 mol%, 55 mol% to less than or equal to 65 mol%, 56 mol% to less than or equal to 64 mol%, 57 mol% to less than or equal to 63 mol%, 58 mol% to less than or equal to 62 mol%, 59 mol% to less than or equal to 61 mol%, 60 mol%, or any subrange formed by any of these endpoints. In some embodiments, the glass-based substrate can include SiO2 in an amount of greater than or equal to 55 mol% to less than or equal to 69 mol%, for example, greater than or equal to 58 mol% to less than or equal to 63 mol%, or any subrange formed by any of these endpoints.
[0084] Glass-based substrates can include any suitable amount of Al2O3. Similar to SiO2, Al2O3 can have the effect of a glass network former. Al2O3 can increase the viscosity of the glass composition because it is tetrahedrally coordinated in the glass melt formed by the glass composition, and when the amount of Al2O3 is too high, the formability of the glass composition is reduced. However, when the concentration of Al2O3 is balanced with the concentration of SiO2 and the concentration of alkali oxides in the glass composition, Al2O3 will reduce the liquidus temperature of the glass melt, thereby enhancing the liquidus viscosity and improving the compatibility of the glass composition with certain forming processes (such as fusion forming processes). Including Al2O3 in a glass-based substrate prevents phase separation and reduces the number of non-bridging oxygens (NBO) in the glass. In addition, Al2O3 can improve the efficiency of ion exchange. In some embodiments, the glass-based substrate may include Al2O3 in an amount of greater than or equal to 3 mol% to less than or equal to 20 mol%, for example, greater than or equal to 4 mol% to less than or equal to 19 mol%, greater than or equal to 5 mol% to less than or equal to 18 mol%, greater than or equal to 6 mol% to less than or equal to 17 mol%, greater than or equal to 7 mol% to less than or equal to 16 mol%, greater than or equal to 8 mol% to less than or equal to 15 mol%, greater than or equal to 9 mol% to less than or equal to 14 mol%, greater than or equal to 10 mol% to less than or equal to 13 mol%, greater than or equal to 11 mol% to less than or equal to 12 mol%, or any sub-range formed by any of these endpoints. In some embodiments, the glass-based substrate may include Al2O3 in an amount of greater than or equal to 5 mol% to less than or equal to 15 mol%, for example, greater than or equal to 7 mol% to less than or equal to 14 mol%, or any sub-range formed by any of these endpoints.
[0085] The glass-based substrate may contain any amount of P2O5 sufficient to produce the desired hydrogen diffusivity. Regardless of the ion pairs that are exchanged, the inclusion of phosphorus in the glass-based substrate facilitates faster interdiffusion. Therefore, the phosphorus-containing glass-based substrate enables efficient formation of glass-based products containing hydrogen-containing layers. The inclusion of P2O5 also enables the production of glass-based products with deep layer depths (e.g., greater than about 10 μm) in a shorter processing time. In some embodiments, the amount of P2O5 contained in the glass-based substrate may be greater than or equal to 4 mol% to less than or equal to 15 mol%, for example: greater than or equal to 5 mol% to less than or equal to 14 mol%, greater than or equal to 6 mol% to less than or equal to 13 mol%, greater than or equal to 7 mol% to less than or equal to 12 mol%, greater than or equal to 8 mol% to less than or equal to 11 mol%, greater than or equal to 9 mol% to less than or equal to 10 mol%, or any sub-range formed by any of these endpoint values. In some embodiments, the glass-based substrate may include P2O5 in an amount of greater than or equal to 5 mol% to less than or equal to 15 mol%, for example, greater than or equal to 6 mol% to less than or equal to 15 mol%, greater than or equal to 5 mol% to less than or equal to 10 mol%, greater than or equal to 6 mol% to less than or equal to 10 mol%, greater than or equal to 7 mol% to less than or equal to 10 mol%, or any sub-range formed by any of these endpoint values.
[0086] The glass-based substrate may include any suitable amount of alkali oxides. Alkali oxides promote ion exchange. The sum of alkali oxides in the glass composition (e.g., Li2O, Na2O, and K2O, as well as other alkali oxides, including Cs2O and Rb2O) may be referred to as "RO", and RO may be expressed as a mole %. In some embodiments, the glass-based substrate may be substantially free of or free of at least one of lithium and sodium. In some embodiments, the glass composition includes R2O in an amount greater than or equal to 6 mol%, for example, greater than or equal to 7 mol%, greater than or equal to 8 mol%, greater than or equal to 9 mol%, greater than or equal to 10 mol%, greater than or equal to 11 mol%, greater than or equal to 12 mol%, greater than or equal to 13 mol%, greater than or equal to 14 mol%, greater than or equal to 15 mol%, greater than or equal to 16 mol%, greater than or equal to 17 mol%, greater than or equal to 18 mol%, greater than or equal to 19 mol%, greater than or equal to 20 mol%, greater than or equal to 21 mol%, greater than or equal to 22 mol%, greater than or equal to about 23 mol%, or greater than or equal to 24 mol%. In one or more embodiments, the glass composition includes R2O in an amount of less than or equal to 25 mol%, such as less than or equal to 24 mol%, less than or equal to 23 mol%, less than or equal to 22 mol%, less than or equal to 21 mol%, less than or equal to 20 mol%, less than or equal to 19 mol%, less than or equal to 18 mol%, less than or equal to 17 mol%, less than or equal to 16 mol%, less than or equal to 15 mol%, less than or equal to about 14 mol%, less than or equal to 13 mol%, less than or equal to 12 mol%, less than or equal to 11 mol%, less than or equal to 10 mol%, less than or equal to 9 mol%, less than or equal to 8 mol%, or less than or equal to 7 mol%. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges. In some embodiments, the glass composition includes R2O in an amount of greater than or equal to 6.0 mol% to less than or equal to 25.0 mol%, for example, greater than or equal to 7.0 mol% to less than or equal to 24.0 mol%, greater than or equal to 8.0 mol% to less than or equal to 23.0 mol%, greater than or equal to 9.0 mol% to less than or equal to 22.0 mol%, greater than or equal to 10.0 mol% to less than or equal to 21.0 mol%, greater than or equal to 11.0 mol% to less than or equal to 20.0 mol%, greater than or equal to about 12.0 mol% to less than or equal to 19.0 mol%, greater than or equal to 13.0 mol% to less than or equal to 18.0 mol%, greater than or equal to 14.0 mol% to less than or equal to 17.0 mol%, or greater than or equal to 15.0 mol% to less than or equal to 16.0 mol%, and all ranges and sub-ranges therebetween.
[0087] In some embodiments, the alkali metal oxide may be KO. The inclusion of KO allows for efficient exchange of hydrogen species into the glass substrate after exposure to an aqueous environment. In an embodiment, the glass-based substrate may include KO in an amount of greater than or equal to 6 mol% to less than or equal to 25 mol%, such as greater than or equal to 7 mol% to less than or equal to 24 mol%, greater than or equal to 8 mol% to less than or equal to 23 mol%, greater than or equal to 9 mol% to less than or equal to 22 mol%, greater than or equal to 10 mol% to less than or equal to 21 mol%, greater than or equal to 11 mol% to less than or equal to 20 mol%, greater than or equal to 12 mol% to less than or equal to 19 mol%, greater than or equal to 13 mol% to less than or equal to 18 mol%, greater than or equal to 14 mol% to less than or equal to 17 mol%, greater than or equal to 15 mol% to less than or equal to 16 mol%, or any subrange formed by any of these endpoint values. In some embodiments, the glass-based substrate may include KO in an amount of greater than or equal to 10 mol% to less than or equal to 25 mol%, for example, greater than or equal to 10 mol% to less than or equal to 20 mol%, greater than or equal to 11 mol% to less than or equal to 25 mol%, greater than or equal to 11 mol% to less than or equal to 20 mol%, greater than or equal to 15 mol% to less than or equal to 20 mol%, or any subrange formed by any of these endpoint values.
[0088] The glass-based substrate may include any suitable amount of Rb2O. In some embodiments, the glass-based substrate may include Rb2O in an amount of greater than or equal to 0 mol% to less than or equal to 10 mol%, for example, greater than or equal to 1 mol% to less than or equal to 9 mol%, greater than or equal to 2 mol% to less than or equal to 8 mol%, greater than or equal to 3 mol% to less than or equal to 7 mol%, greater than or equal to 4 mol% to less than or equal to 6 mol%, 5 mol%, or any sub-range formed by any of these endpoint values.
[0089] The glass-based substrate may include any suitable amount of Cs2O. In some embodiments, the glass-based substrate may include Cs2O in an amount of greater than or equal to 0 mol% to less than or equal to 10 mol%, for example, greater than or equal to 1 mol% to less than or equal to 9 mol%, greater than or equal to 2 mol% to less than or equal to 8 mol%, greater than or equal to 3 mol% to less than or equal to 7 mol%, greater than or equal to 4 mol% to less than or equal to 6 mol%, 5 mol%, or any sub-range formed by any of these endpoint values.
[0090] In some embodiments, the glass-based substrate may have a composition comprising greater than or equal to 45 mol% to less than or equal to 75 mol% SiO2, greater than or equal to 3 mol% to less than or equal to 20 mol% Al2O3, greater than or equal to 6 mol% to less than or equal to 15 mol% P2O5, and greater than or equal to 6 mol% to less than or equal to 25 mol% K2O.
[0091] In some embodiments, the glass-based substrate may have a composition comprising greater than or equal to 45 mol % to less than or equal to 75 mol % SiO2, greater than or equal to 3 mol % to less than or equal to 20 mol % Al2O3, greater than or equal to 4 mol % to less than or equal to 15 mol % P2O5, and greater than or equal to 11 mol % to less than or equal to 25 mol % K2O.
[0092] In some embodiments, the glass-based substrate may have a composition comprising greater than or equal to 55 mol % to less than or equal to 69 mol % SiO2, greater than or equal to 5 mol % to less than or equal to 15 mol % Al2O3, greater than or equal to 6 mol % to less than or equal to 10 mol % P2O5, and greater than or equal to 10 mol % to less than or equal to 20 mol % K2O.
[0093] In some embodiments, the glass-based substrate may have a composition comprising greater than or equal to 55 mol % to less than or equal to 69 mol % SiO2, greater than or equal to 5 mol % to less than or equal to 15 mol % Al2O3, greater than or equal to 5 mol % to less than or equal to 10 mol % P2O5, and greater than or equal to 11 mol % to less than or equal to 20 mol % K2O.
[0094] In some embodiments, the glass-based substrate may have a composition comprising greater than or equal to 58 mol % to less than or equal to 63 mol % SiO2, greater than or equal to 7 mol % to less than or equal to 14 mol % Al2O3, greater than or equal to 7 mol % to less than or equal to 10 mol % P2O5, and greater than or equal to 15 mol % to less than or equal to 20 mol % K2O.
[0095] In some embodiments, the glass-based substrate may exhibit a Vickers crack initiation threshold of 5 kgf or greater, such as 6 kgf or greater, 7 kgf or greater, 8 kgf or greater, 9 kgf or greater, 10 kgf or greater, or greater.
[0096] The glass-based substrate may have any suitable geometric morphology. In some embodiments, the thickness of the glass-based substrate may be less than or equal to 2 mm, for example, less than or equal to 1 mm, less than or equal to 900 μm, less than or equal to 800 μm, less than or equal to 700 μm, less than or equal to 600 μm, less than or equal to 500 μm, less than or equal to 400 μm, less than or equal to 300 μm, or less. In some embodiments, the glass-based substrate may be flat or sheet-like in shape. In some other embodiments, the glass-based substrate may have a 2.5D or 3D shape. As used herein, "2.5D shape" refers to a sheet-like product having at least one major surface that is at least partially non-planar and a substantially flat second major surface. As used herein, "3D shape" refers to a product having first and second opposing major surfaces that are at least partially non-planar.
[0097] A glass-based article may be produced from a glass-based substrate by exposure to water vapor under any suitable conditions. Exposure may be performed in any suitable apparatus, such as an oven with relative humidity control. In some embodiments, the glass-based substrate may be exposed to an environment with a relative humidity greater than or equal to 75%, such as greater than or equal to 80%, greater than or equal to 85%, greater than or equal to 90%, greater than or equal to 95%, greater than or equal to 99%, or greater. In some embodiments, the glass-based substrate may be exposed to an environment with a relative humidity of 100%.
[0098] In some embodiments, the glass-based substrate can be exposed to an environment at a temperature of 70°C or greater, for example, 75°C or greater, 80°C or greater, 85°C or greater, 90°C or greater, 95°C or greater, 100°C or greater, 105°C or greater, 110°C or greater, 115°C or greater, 120°C or greater, 125°C or greater, 130°C or greater, 135°C or greater, 140°C or greater, 145°C or greater, 150°C or greater, 155°C or greater, 160°C or greater, 160°C or greater, 165°C or greater, 170°C or greater, 175°C or greater, 180°C or greater, 185°C or greater, 190°C or greater, 195°C or greater, 200°C or greater, or higher. In some embodiments, the glass-based substrate can be exposed to an environment at a temperature of greater than or equal to 70°C to less than or equal to 210°C, for example, greater than or equal to 75°C to less than or equal to 205°C, greater than or equal to 80°C to less than or equal to 200°C, greater than or equal to 85°C to less than or equal to 195°C, greater than or equal to 90°C to less than or equal to 190°C, greater than or equal to 95°C to less than or equal to 185°C, greater than or equal to 100°C to less than or equal to 180°C. , greater than or equal to 105°C to less than or equal to 175°C, greater than or equal to 110°C to less than or equal to 170°C, greater than or equal to 115°C to less than or equal to 165°C, greater than or equal to 120°C to less than or equal to 160°C, greater than or equal to 125°C to less than or equal to 155°C, greater than or equal to 130°C to less than or equal to 150°C, greater than or equal to 135°C to less than or equal to 145°C, 140°C, or any sub-range formed by any of these endpoint values.
[0099] In some embodiments, the glass-based substrate may be exposed to an environment containing water vapor for a period of time sufficient to produce the desired degree of diffusion of hydrogen-containing species and the desired depth of layer. In some embodiments, the glass-based substrate may be exposed to an environment containing water vapor for a period of time greater than or equal to 1 day, such as greater than or equal to 2 days, greater than or equal to 3 days, greater than or equal to 4 days, greater than or equal to 5 days, greater than or equal to 6 days, greater than or equal to 7 days, greater than or equal to 8 days, greater than or equal to 9 days, greater than or equal to 10 days, greater than or equal to 15 days, greater than or equal to 20 days, greater than or equal to 25 days, greater than or equal to 30 days, greater than or equal to 35 days, greater than or equal to 40 days, greater than or equal to 45 days, greater than or equal to 50 days, greater than or equal to 55 days, greater than or equal to 60 days, greater than or equal to 65 days, or longer. In some embodiments, the glass-based substrate may be exposed to the water vapor-containing environment for a duration of greater than or equal to 1 day to less than or equal to 70 days, such as greater than or equal to 2 days to less than or equal to 65 days, greater than or equal to 3 days to less than or equal to 60 days, greater than or equal to 4 days to less than or equal to 55 days, greater than or equal to 5 days to less than or equal to 45 days, greater than or equal to 6 days to less than or equal to 40 days, greater than or equal to 7 days to less than or equal to 35 days, greater than or equal to 8 days to less than or equal to 30 days, greater than or equal to 9 days to less than or equal to 25 days, greater than or equal to 10 days to less than or equal to 20 days, 15 days, or any subrange formed by any of these endpoints. The exposure conditions may be varied to reduce the time required to produce a desired amount of hydrogen-containing species diffusion into the glass-based substrate. For example, the temperature and / or relative humidity may be increased to reduce the time required to achieve a desired degree of hydrogen-containing species diffusion and layer depth into the glass-based substrate.
[0100] The glass-based articles disclosed herein can be integrated into another article, such as an article with a display screen (or display article) (e.g., consumer electronics, including mobile phones, tablets, computers, navigation systems, and wearable devices (such as watches), etc.), a building article, a transportation article (e.g., a vehicle, a train, an aircraft, a marine vehicle, etc.), an electrical article, or any article requiring partial transparency, scratch resistance, abrasion resistance, or a combination thereof. Exemplary articles incorporating any of the glass-based articles disclosed herein are as follows: Figure 2A and 2B Specifically, Figure 2A and 2BA consumer electronic device 200 is shown, comprising: a housing 202 having a front surface 204, a back surface 206, and side surfaces 208; an electronic assembly (not shown) at least partially or completely within the housing and including at least a controller, a memory, and a display 210 located at or adjacent to the front surface of the housing; and a cover substrate 212 located at or above the front surface of the housing so that it is located above the display. In some embodiments, at least a portion of one of the cover substrate 212 and the housing 202 can include any glass-based article disclosed herein.
[0101] Exemplary Embodiments
[0102] Glass compositions particularly suitable for forming glass-based articles described herein are formed into glass-based substrates. Table II below describes the compositions of Examples 1-6. Density was determined using the buoyancy method of ASTM C693-93 (2013). The linear coefficient of thermal expansion (CTE) over the temperature range of 25°C to 300°C is expressed as 10 -7 / ° C, and determined using a push rod dilatometer according to ASTM E228-11. The strain point and annealing point were determined using the beam bending viscosity method of ASTM C598-93 (2013). The softening point was determined using the parallel plate viscosity method of ASTM C1351M-96 (2012). According to ASTM C965-96 (2012) entitled "Standard Practice for Measuring Viscosity of Glass Above the Softening Point", the temperature at which the glass of the resulting composition has a viscosity of 200P, 35000P and 200000P was measured.
[0103] Table II
[0104]
[0105]
[0106] A glass-based substrate comprising the composition of Example 1 and having a thickness of 1 mm was exposed to an environment of 85% relative humidity for 65 days to form a glass-based article comprising a hydrogen-containing layer of the type described herein.
[0107] The depth of the hydrogen-containing layer was measured by SIMS before and after exposure. The SIMS hydrogen concentration measurement results are shown in Figure 2. Figure 3As shown, the as-received glass-based substrate hydrogen concentration curve 301 has a layer depth of about 5 μm, and the glass-based article hydrogen concentration curve 302 has a layer depth of about 30 μm. The exposed glass-based article was measured to a depth of about 25 μm, and the curve 303 was extrapolated to determine the layer depth. Based on the measured values, the hydrogen diffusivity (D) was calculated using the general formula DOL = square root (D·time).
[0108] The Vickers indentation cracking threshold was measured before and after exposure to an environment containing water vapor. The Vickers indentation results for the glass-based substrate before exposure are shown in Figure 2. Figure 4 and 5 As shown in the figure, they are after indentation at 5kgf and 10kgf respectively. Figure 4 and 5 As shown in FIG. 1 , the glass-based substrate has a Vickers crack initiation threshold higher than 5 kgf but lower than 10 kgf. The Vickers indentation results of the glass-based article after exposure are shown in FIG. Figure 6 , 7 8 are shown after indentation at 5kgf, 10kgf and 20kgf respectively. Figure 6 , 7 As demonstrated by Figures 1 and 8, the Vickers indentation cracking threshold of the glass-based article is greater than 20 kgf.
[0109] A glass-based substrate comprising the composition of Comparative Examples 1 to 3 and having a thickness of 1 mm was also prepared and exposed to an environment of 85% relative humidity for 30 days. The compositions of Comparative Examples 1 to 3 are recorded in Table III below. The Vickers indentation cracking threshold was measured before and after exposure to an environment containing water vapor, and the depth of the hydrogen-containing layer after exposure was measured by SIMS. The hydrogen diffusivity was calculated based on the measured values.
[0110] Table III
[0111]
[0112] As shown in Table III, the glass composition of Example 1 exhibits hydrogen diffusivity that is 2 orders of magnitude higher than that of Comparative Example 3, which also contains potassium but does not contain phosphorus. These results indicate that the presence of phosphorus in the glass composition significantly increases hydrogen diffusivity. Similarly, the glass composition of Comparative Example 3 exhibits hydrogen diffusivity that is 2 orders of magnitude higher than that of Comparative Examples 1 and 2, which contain lithium and sodium, respectively. The difference in hydrogen diffusivity between the potassium-containing glass composition and the lithium- and sodium-containing glass compositions indicates that alkali ions with larger ionic radii enable faster hydrogen diffusion.
[0113] Glass-based substrates comprising the glass composition of Example 6 were produced with a thickness of 0.5 mm and 1.0 mm. The glass-based substrates were exposed to a 100% relative humidity environment at a temperature of 200° C. for a period of 7 days to produce glass-based articles of the type described herein. The glass-based articles exhibited a compressive stress region extending from the surface to a compression depth. The maximum compressive stress measured for the 0.5 mm glass-based article was 124 MPa, while the maximum compressive stress measured for the 1.0 mm glass-based article was 137 MPa. The maximum central tension measured for the 0.5 mm glass-based article was 32 MPa, while the maximum central tension measured for the 1.0 mm glass-based article was 15 MPa. The compression depth measured for the 0.5 mm glass-based article was 101 μm, while the compression depth measured for the 1.0 mm glass-based article was 99 μm.
[0114] Samples were cut from the center of 0.5 mm and 1.0 mm thick glass-based articles formed after a glass-based substrate comprising the glass of Example 6 was exposed to a 100% relative humidity environment at 200° C. for 7 days. The samples were then polished to 0.5 mm width and subjected to Fourier transform infrared spectroscopy (FTIR) analysis. FTIR analysis was performed under the following conditions: CaF / InSb, 64 scans, 16 cm -1 Resolution, 10 μm aperture, and 10 μm step. Scans were started at the sample surface and continued to approximately mid-thickness. Spectra were analyzed relative to “dry” silica and using 3900 cm -1 Maximum parameters and 3550cm -1 Minimum parameters calculate the hydroxyl (βOH) concentration. Due to the multi-component nature of glass-based products, it is not possible to distinguish bound hydroxyl from molecular hydroxyl, so the graph reports the concentration of the total hydroxyl content. Fig. 9 and 10 The hydroxyl concentration curves measured for samples with a thickness of 0.5 mm and 1.0 mm are shown respectively. Fig. 9 and 10 As shown, the depth at which the measured hydroxyl content within the sample becomes substantially constant and equal to the hydroxyl content at the center of the article (indicating the background hydroxyl content of the precursor glass-based substrate) is approximately 200 μm as measured by FTIR. Fig. 9 and 10 The buried hydroxyl concentration peak that appears in the graph is an artifact of the measurement method.
[0115] Square samples having the composition of Example 1 were prepared with a thickness of 1 mm and a side of 50 mm. Five of these samples were then treated in a 100% relative humidity environment at 200°C for 121 hours. The compressive stress (CS) and depth of compression (DOC) obtained for the treated samples were then measured using FSM, and the CS was 167 MPa and the DOC was 73 μm. These five steam-treated samples and three control samples that were not exposed to steam treatment were then subjected to an abrasion ring-on-ring (AROR) test. The strength and peak load of each test sample are recorded in Table IV. As shown in Table IV, the steam-treated samples exhibited significantly increased peak load and strength compared to the untreated control samples.
[0116] Table IV
[0117]
[0118]
[0119] The AROR test is a surface strength measurement used to test flat glass specimens, and ASTM C1499-09 (2013), entitled "Standard Test Method for Monotonic Equibiaxial Flexural Strength of Advanced Ceramics at Ambient Temperature", serves as the basis for the AROR test method used herein. The entire contents of ASTM C1499-09 are incorporated herein by reference. Prior to the ring-on-ring test, the glass specimens were abraded with 90 mesh silicon carbide (SiC) particles, and the particles were transferred to the glass samples using the methods and equipment described in Appendix A2 (entitled "abrasion Procedures") of ASTM C158-02 (2012), entitled "Standard Test Methods for Strength of Glass by Flexure (Determination of Modulus of Rupture)". The entire contents of ASTM C158-02, particularly Appendix A2, are incorporated herein by reference.
[0120] Prior to the ring-on-ring test, the surface of the glass-based article sample was abraded as described in Appendix 2 of ASTM C158-02 using the apparatus shown in Figure A2.1 of ASTM C158-02 to standardize and / or control the surface defect state of the sample. The abrasive was blasted onto the surface of the glass-based article at an air pressure of 5 psi. After the air flow was established, a 1 cm 3 The abrasive is poured into the furnace and the sample is sandblasted.
[0121] For the AROR test, a glass-based article having at least one abrasion surface is placed between two concentric rings of different sizes to determine the equibiaxial flexural strength (i.e., the maximum stress that the material can sustain when subjected to flexure between two concentric rings), such as Fig.11 Schematically shown. In the AROR configuration 400, the worn glass-based article 410 is supported by a support ring 420 having a diameter D2. A force F is applied to the surface of the glass-based article via a load ring 430 having a diameter D1 by a dynamometer (not shown).
[0122] The ratio of the diameters of the load ring to the support ring D1 / D2 may be 0.2 to 0.5. In some embodiments, D1 / D2 is 0.5. The load ring and support rings 430, 420 should be concentrically aligned within 0.5% of the support ring diameter D2. The dynamometer used for testing should be accurate within ±1% of the selected range at any load. Tests were conducted at a temperature of 23±2°C and a relative humidity of 40±10%.
[0123] For fixture design, the radius r of the protruding surface of the load ring 430 is h / 2≤r≤3h / 2, where h is the thickness of the glass-based article 410. The load ring and support rings 430 and 420 are made of hardness HR c Made of hardened steel >40. AROR fixtures are commercially available.
[0124] The target failure mechanism of the AROR test is to observe the breakage of the glass-based article 410 originating from the surface 430a within the load ring 430. For data analysis, failures existing outside this area (i.e., between the load ring 430 and the support ring 420) are ignored. However, due to the thinness and high strength of the glass-based article 410, large deflections exceeding 1 / 2 of the specimen thickness h are sometimes observed. Therefore, a high percentage of failures originating from below the load ring 430 are often observed. It is impossible to accurately calculate stress without understanding the stress development and failure sources within and under the ring of each specimen (collectively referred to as analysis by strain gauges). Therefore, the AROR test focuses on the peak load of failure when measuring the response.
[0125] Although typical embodiments are provided for illustrative purposes, the foregoing description should not be considered as limiting the scope of this specification or the appended claims. Therefore, various improvements, modifications and alternative forms may be conceived by those skilled in the art without departing from the spirit and scope of this specification or the appended claims.
[0126] This application also relates to the following items.
[0127] 1. A glass-based article comprising:
[0128] SiO2, Al2O3 and P2O5; and
[0129] a hydrogen-containing layer extending from a surface of the glass-based article to a depth of layer,
[0130] in,
[0131] The hydrogen concentration of the hydrogen-containing layer decreases from a maximum hydrogen concentration to the depth of the layer; and
[0132] The layer depth is greater than 5 μm.
[0133] 2. The glass-based article of item 1, wherein the glass-based article has a Vickers crack initiation threshold of at least 1 kgf.
[0134] 3. The glass-based article of item 1 or 2, wherein the depth of layer is at least about 10 μm.
[0135] 4. The glass-based article of any one of items 1 to 3, wherein the maximum hydrogen concentration is located at a surface of the glass-based article.
[0136] 5. The glass-based article of any one of items 1 to 4, further comprising at least one of: Li2O, Na2O, K2O, Cs2O, and Rb2O.
[0137] 6. The glass-based article of any one of items 1 to 5, further comprising K2O.
[0138] 7. The glass-based article of any one of items 1 to 6, wherein the center of the glass-based article comprises:
[0139] Greater than or equal to 45 mol % and less than or equal to 75 mol % SiO2;
[0140] 3 mol% or more and 20 mol% or less Al2O3;
[0141] 6 mol % or more and 15 mol % or less P2O5; and
[0142] Greater than or equal to 6 mol % and less than or equal to 25 mol % K2O.
[0143] 8. The glass-based article of any one of items 1 to 6, wherein the center of the glass-based article comprises:
[0144] Greater than or equal to 45 mol % and less than or equal to 75 mol % SiO2;
[0145] 3 mol% or more and 20 mol% or less Al2O3;
[0146] Greater than or equal to 4 mol % to less than or equal to 15 mol % P2O5; and
[0147] Greater than or equal to 11 mol % and less than or equal to 25 mol % K2O.
[0148] 9. The glass-based article of any one of items 1 to 6, wherein the center of the glass-based article comprises:
[0149] 55 mol% or more and 69 mol% or less SiO2;
[0150] 5 mol% or more and 15 mol% or less Al2O3;
[0151] 6 mol % or more and 10 mol % or less P2O5; and
[0152] Greater than or equal to 10 mol % and less than or equal to 20 mol % K2O.
[0153] 10. The glass-based article of any one of items 7 to 9, wherein the center of the glass-based article comprises:
[0154] Greater than or equal to 0 mol % to less than or equal to 10 mol % Cs2O; and
[0155] Greater than or equal to 0 mol % to less than or equal to 10 mol % Rb2O.
[0156] 11. The glass-based article of any of items 1 to 10, wherein the glass-based article is substantially free of at least one of lithium and sodium.
[0157] 12. The glass-based article of any of items 1 to 11, further comprising a compressive stress layer extending from a surface of the glass-based article into the glass-based article to a compressive depth.
[0158] 13. The glass-based article of item 12, wherein the compressive stress layer comprises a compressive stress greater than or equal to 100 MPa and a compression depth greater than or equal to 75 μm.
[0159] 14. A consumer electronic product comprising:
[0160] a housing including a front surface, a back surface, and a side surface;
[0161] an electronic assembly at least partially located within the housing, the electronic assembly including at least a controller, a memory, and a display, the display being located at or adjacent to the front surface of the housing; and
[0162] a cover substrate disposed over the display,
[0163] wherein at least a portion of at least one of the housing or the covering substrate comprises a glass-based article as described in any one of items 1 to 13.
[0164] 15. A glass comprising:
[0165] Greater than or equal to 45 mol % and less than or equal to 75 mol % SiO2;
[0166] 3 mol% or more and 20 mol% or less Al2O3;
[0167] 6 mol % or more and 15 mol % or less P2O5; and
[0168] Greater than or equal to 6 mol % and less than or equal to 25 mol % K2O.
[0169] 16. The glass according to item 15, comprising:
[0170] 55 mol% or more and 69 mol% or less SiO2;
[0171] 5 mol% or more and 15 mol% or less Al2O3;
[0172] 6 mol % or more and 10 mol % or less P2O5; and
[0173] Greater than or equal to 10 mol % and less than or equal to 20 mol % K2O.
[0174] 17. The glass according to item 15 or 16, further comprising:
[0175] Greater than or equal to 0 mol % to less than or equal to 10 mol % Cs2O; and
[0176] Greater than or equal to 0 mol % to less than or equal to 10 mol % Rb2O.
[0177] 18. The glass of any one of items 15 to 17, wherein the glass is substantially free of lithium.
[0178] 19. The glass of any one of items 15 to 18, wherein the glass is substantially free of sodium.
[0179] 20. The glass according to any one of items 15 to 19, comprising:
[0180] 58 mol% or more and 63 mol% or less SiO2;
[0181] 7 mol% or more and 14 mol% or less Al2O3;
[0182] 7 mol % or more and 10 mol % or less P2O5; and
[0183] Greater than or equal to 15 mol % and less than or equal to 20 mol % K2O.
[0184] 21. The glass according to any one of items 15 to 20, wherein the glass has a Vickers crack initiation threshold greater than or equal to 5 kgf.
[0185] 22. The glass of any one of items 15 to 17, 20 and 21, further comprising at least one of: Li2O, Na2O, Cs2O and Rb2O.
[0186] 23. A glass comprising:
[0187] Greater than or equal to 45 mol % and less than or equal to 75 mol % SiO2;
[0188] 3 mol% or more and 20 mol% or less Al2O3;
[0189] Greater than or equal to 4 mol % to less than or equal to 15 mol % P2O5; and
[0190] Greater than or equal to 11 mol % and less than or equal to 25 mol % K2O.
[0191] 24. The glass according to item 23, comprising:
[0192] 55 mol% or more and 69 mol% or less SiO2;
[0193] 5 mol% or more and 15 mol% or less Al2O3;
[0194] Greater than or equal to 5 mol % to less than or equal to 10 mol % P2O5; and
[0195] Greater than or equal to 11 mol % and less than or equal to 20 mol % K2O.
[0196] 25. The glass according to item 23 or 24, further comprising:
[0197] Greater than or equal to 0 mol % to less than or equal to 10 mol % Cs2O; and
[0198] Greater than or equal to 0 mol % to less than or equal to 10 mol % Rb2O.
[0199] 26. The glass of any one of items 23 to 25, wherein the glass is substantially free of lithium.
[0200] 27. The glass of any one of items 23 to 26, wherein the glass is substantially free of sodium.
[0201] 28. The glass according to any one of items 23 to 27, comprising:
[0202] 58 mol% or more and 63 mol% or less SiO2;
[0203] 7 mol% or more and 14 mol% or less Al2O3;
[0204] 7 mol % or more and 10 mol % or less P2O5; and
[0205] Greater than or equal to 15 mol % and less than or equal to 20 mol % K2O.
[0206] 29. The glass according to any one of items 23 to 28, wherein the glass has a Vickers crack initiation threshold greater than or equal to 5 kgf.
[0207] 30. The glass of any one of items 23 to 25, 28 and 29, further comprising at least one of the following: Li2O, Na2O, Cs2O and Rb2O.
[0208] 31. A method comprising:
[0209] exposing a glass-based substrate to an environment having a relative humidity of greater than or equal to 75% to form a glass-based article having a hydrogen-containing layer extending from a surface of the glass-based article to a depth of layer,
[0210] in,
[0211] Glass-based substrates contain SiO2, Al2O3 and P2O5.
[0212] The hydrogen concentration of the hydrogen-containing layer decreases from a maximum hydrogen concentration to the depth of the layer; and
[0213] The layer depth is greater than or equal to 5 μm.
[0214] 32. The method of claim 31, wherein the glass-based substrate has a composition comprising:
[0215] 55 mol% or more and 69 mol% or less SiO2;
[0216] 5 mol% or more and 15 mol% or less Al2O3;
[0217] 6 mol % or more and 10 mol % or less P2O5; and
[0218] Greater than or equal to 10 mol % and less than or equal to 20 mol % K2O.
[0219] 33. The method of claim 31, wherein the glass-based substrate has a composition comprising:
[0220] Greater than or equal to 45 mol % and less than or equal to 75 mol % SiO2;
[0221] 3 mol% or more and 20 mol% or less Al2O3;
[0222] Greater than or equal to 4 mol % to less than or equal to 15 mol % P2O5; and
[0223] Greater than or equal to 11 mol % and less than or equal to 25 mol % K2O.
[0224] 34. The method of claim 31, wherein the glass-based substrate has a composition comprising:
[0225] Greater than or equal to 45 mol % and less than or equal to 75 mol % SiO2;
[0226] 3 mol% or more and 20 mol% or less Al2O3;
[0227] 6 mol % or more and 15 mol % or less P2O5; and
[0228] Greater than or equal to 6 mol % and less than or equal to 25 mol % K2O.
[0229] 35. The method of any one of items 31 to 34, wherein the glass-based substrate further comprises:
[0230] Greater than or equal to 0 mol % to less than or equal to 10 mol % Cs2O; and
[0231] Greater than or equal to 0 mol % to less than or equal to 10 mol % Rb2O.
[0232] 36. The method of any one of items 31 to 35, further comprising at least one of: Li2O, Na2O, Cs2O and Rb2O.
[0233] 37. The method of any one of items 31 to 36, wherein the glass-based substrate is substantially free of at least one of lithium and sodium.
[0234] 38. The method of any one of items 31 to 37, wherein the exposure occurs at a temperature greater than or equal to 70°C.
[0235] 39. The method of any one of items 31 to 38, wherein the glass-based article has a Vickers crack initiation threshold greater than or equal to 1 kgf.
Claims
1. A glass-based article comprising: a hydrogen-containing layer extending from the surface of the glass-based article to a layer depth, wherein the hydrogen concentration of the hydrogen-containing layer decreases from a maximum hydrogen concentration to a depth of the layer; wherein the layer depth is greater than 5 μm; and wherein the center of the glass-based article comprises: SiO2; Al2O3; 4 mol% or more and 15 mol% or less of P2O5; 6 mol % or more and 25 mol % or less of R2O, wherein R2O refers to the sum of alkali metal oxides, It also includes a compressive stress layer extending from a surface of the glass-based article into the glass-based article to a compressive depth, wherein the compressive stress layer is generated by hydrogen-containing ions.
2. The glass-based article of claim 1, wherein the R2O comprises K2O.
3. The glass-based article of claim 2, wherein the K2O is greater than or equal to 6 mol% to less than or equal to 25 mol%.
4. The glass-based article of claim 1 or 2, wherein the maximum hydrogen concentration is located at a surface of the glass-based article.
5. The glass-based article of claim 1 or 2, wherein the R2O further comprises at least one of Na2O, Cs2O, and Rb2O.
6. The glass-based article of claim 1 or 2, wherein the center of the glass-based article comprises: 45 mol% or more and 75 mol% or less of SiO2; 3 mol% or more and 20 mol% or less of Al2O3; 4 mol % or more and 15 mol % or less of P2O5; and Greater than or equal to 11 mol % and less than or equal to 25 mol % R2O.
7. The glass-based article of claim 1 or 2, wherein the center of the glass-based article comprises: 0 mol % or more and 10 mol % or less of Cs2O; and Greater than or equal to 0 mol % and less than or equal to 10 mol % Rb2O.
8. The glass-based article of claim 1 or 2, wherein the glass-based article is substantially free of lithium, such that the lithium is less than 0.01 mol%.
9. The glass-based article of claim 1, wherein the compressive stress layer comprises a compressive stress greater than or equal to 100 MPa.
10. The glass-based article of claim 1, wherein the compression depth is greater than or equal to 75 μm.
11. A consumer electronic product comprising: a housing including a front surface, a back surface, and a side surface; an electronic assembly at least partially disposed within the housing, the electronic assembly comprising at least a controller, a memory, and a display, the display being disposed on or adjacent to the front surface of the housing; as well as a cover substrate disposed over the display, Wherein at least a portion of at least one of the housing or the cover substrate comprises the glass-based article of claim 1 or 2.
12. A glass-based article comprising: a hydrogen-containing layer extending from a surface of the glass-based article to a depth of layer; a compressive stress layer extending from a surface of the glass-based article to a compressive depth, wherein the compressive stress layer is generated by hydrogen-containing ions, wherein the compressive stress layer comprises a compressive stress greater than or equal to 100 MPa; wherein the center of the glass-based article comprises: SiO2; Al2O3; 4 mol% or more and 15 mol% or less of P2O5; Greater than or equal to 6 mol % to less than or equal to 25 mol % R2O, wherein R2O refers to the sum of alkali metal oxides.
13. The glass-based article of claim 12, wherein the R2O comprises K2O.
14. The glass-based article of claim 13, wherein the K2O is greater than or equal to 6 mol% to less than or equal to 25 mol%.
15. The glass-based article of claim 12 or 13, wherein a maximum hydrogen concentration is located at a surface of the glass-based article and a hydrogen concentration of the hydrogen-containing layer decreases from the maximum hydrogen concentration to the layer depth.
16. The glass-based article of claim 12 or 13, wherein the R2O further comprises at least one of Na2O, Cs2O, and Rb2O.
17. The glass-based article of claim 12 or 13, wherein the center of the glass-based article comprises: 45 mol% or more and 75 mol% or less of SiO2; 3 mol% or more and 20 mol% or less of Al2O3; 4 mol % or more and 15 mol % or less of P2O5; and Greater than or equal to 11 mol % and less than or equal to 25 mol % R2O.
18. The glass-based article of claim 12 or 13, wherein the center of the glass-based article comprises: 0 mol % or more and 10 mol % or less of Cs2O; and Greater than or equal to 0 mol % and less than or equal to 10 mol % Rb2O.
19. The glass-based article of claim 12 or 13, wherein the glass-based article is substantially free of lithium, such that the lithium is less than 0.01 mol%.
20. The glass-based article of claim 12 or 13, wherein the compression depth is greater than or equal to 75 μm.
21. The glass-based article of claim 12 or 13, wherein the compression depth is greater than or equal to 0.05t, where t is the thickness of the glass-based article.
22. The glass-based article of claim 12 or 13 having a thickness of less than 2 mm.
23. The glass-based article of claim 12 or 13 having a 2.5D shape.
24. The glass-based article of claim 12 or 13 having a 3D shape.
25. A consumer electronic product comprising: a housing including a front surface, a back surface, and a side surface; an electronic assembly at least partially disposed within the housing, the electronic assembly comprising at least a controller, a memory, and a display, the display being disposed on or adjacent to the front surface of the housing; as well as a cover substrate disposed over the display, wherein at least a portion of at least one of the housing or the cover substrate comprises the glass-based article of claim 12 or 13.
26. A method of making a glass-based article comprising: exposing the glass-based substrate to water vapor and a temperature greater than or equal to 70° C.; wherein the glass-based substrate comprises SiO2, Al2O3, P2O5 and R2O, wherein R2O refers to the sum of alkali metal oxides, Wherein after the exposing, the glass-based article comprises a compressive stress layer extending from a surface of the glass-based article into the glass-based article to a compressive depth, wherein the compressive stress layer is generated by hydrogen-containing ions.
27. The method of claim 26, wherein the environment comprises a relative humidity greater than or equal to 75%.
28. The method of claim 26 or 27, wherein the P2O5 is greater than or equal to 4 mol% to less than or equal to 15 mol%.
29. The method of claim 26 or 27, wherein the R2O is greater than or equal to 6 mol% to less than or equal to 25 mol%.
30. The method of claim 26 or 27, wherein the R2O comprises K2O.
31. The method of claim 30, wherein the K2O is greater than or equal to 6 mol% to less than or equal to 25 mol%.
32. The method of claim 26 or 27, wherein the R2O is greater than or equal to 11 mol% to less than or equal to 25 mol%.
33. The method of claim 26 or 27, wherein the R2O further comprises at least one of Na2O, Cs2O, and Rb2O.
34. The method of claim 26 or 27, wherein the glass is substantially free of lithium, such that the lithium is less than 0.01 mol%.
35. The method of claim 26 or 27, wherein the R2O comprises Na2O.
36. The method of claim 26 or 27, wherein after the exposing, the glass-based substrate comprises a hydrogen-containing layer extending from a surface of the glass-based article to a depth of layer.
37. The method of claim 36, wherein the layer depth is greater than 5 μm.
38. The method of claim 26, wherein the compressive stress layer comprises a compressive stress greater than or equal to 100 MPa.
39. The method of claim 26, wherein the compression depth is greater than or equal to 75 μm.
40. The method of claim 26, wherein the compression depth is greater than or equal to 0.05 t, where t is the thickness of the glass-based article.
Citation Information
Patent Citations
Reinforced glass, reinforced glass substrate, and method for producing the same
CN101801869A
Ion exchangeable glass with deep compressive layer and high damage threshold
CN103282318A
Methods for enhancing strength and durability of a glass article
US20120277085A1